800score.comhttp://www.800score.com/forum/ GMAT Algebra (Data Sufficiency)http://www.800score.com/forum/viewtopic.php?f=3&t=3198 Page 1 of 1

 Author: questioner [ Tue Mar 27, 2012 7:46 am ] Post subject: GMAT Algebra (Data Sufficiency) What is the value of x² + y²?(1) x + y = 4(2) xy = 2A. Statement (1) BY ITSELF is sufficient to answer the question, but statement (2) by itself is not.B. Statement (2) BY ITSELF is sufficient to answer the question, but statement (1) by itself is not.C. Statements (1) and (2) TAKEN TOGETHER are sufficient to answer the question, even though NEITHER statement BY ITSELF is sufficient.D. Either statement BY ITSELF is sufficient to answer the question.E. Statements (1) and (2) TAKEN TOGETHER are NOT sufficient to answer the question, meaning that further information would be needed to answer the question.(C) If we use statement (1) by itself, we can solve it for x. x = 4 – y. The desired sum, x² + y², equals (4 – y)² + y². We do NOT know the value of y. Therefore we do NOT have a definite value of the desired sum. Statement (1) by itself is NOT sufficient.If we use statement (2) by itself, it implements that y can NOT be 0 and we can solve it for x. x = 2/y. The desired sum, x² + y², is (2/y)² + y². We do NOT know the value of y. Therefore we do NOT have a definite value of the desired sum. Statement (2) by itself is NOT sufficient.If we use the both statements together, let’s manipulate them a little. First, multiply the second one by 2 to get 2xy = 4. Then square the first one. x² + 2xy + y² = 4². Subtract the second one from the first one to get x² + y² = 16 – 4. Therefore the desired sum equals 16 – 4 = 12. Statements (1) and (2) taken together are sufficient to answer the question, even though neither statement by itself is sufficient. The correct answer is C.----------It seems to me that (2) would be correct. If we're looking to find the value of x² + y², all we would need to know is "xy" because:x² + y² = x² + 2xy + y²so: x² + y² = -2xyif xy=2, then -2xy= (-2)2= -4therefore x² + y² =(-4)

 Author: Gennadiy [ Tue Mar 27, 2012 8:14 am ] Post subject: Re: GMAT Algebra (Data Sufficiency) Quote:therefore x² + y² =(-4)The result you got is impossible, because the sum of two squares must be a non-negative number. Therefore there must be a mistake in your reasoning.Here it is:Quote:x² + y² = x² + 2xy + y²so: x² + y² = -2xyThe first equality is true only if one of the variables is 0 because it can be simplified into 0 = 2xy. Probably, you confused it with (x + y)² = x² + 2xy + y², which is true for any values.The second equality does NOT come from the first one. It is the same as x² + 2xy + y² = 0, which is (x + y)² = 0.That is NOT implied by anything in the question statement.

 Author: questioner [ Fri Dec 14, 2012 10:52 am ] Post subject: Re: GMAT Algebra (Data Sufficiency) For statement 1,x + y = 4so x² + y² can be broken down into (x + y)(x + y) which can be replaced from statement 1. Thus it gives a value of 4 × 4 which is 16. I am confused for this question

 Author: Gennadiy [ Fri Dec 14, 2012 11:00 am ] Post subject: Re: GMAT Algebra (Data Sufficiency) Quote:x² + y² can be broken down into (x + y)(x + y)No. (x + y)(x + y) = (x + y)²We can either use the formula for (x + y)² or multiply (x + y)(x + y) to see that(x + y)(x + y) = x² + 2xy + y²Here are the two sets of values that fit Statement (1), but yield different results:x = y = 2(1) x + y = 4 holds true: 2 + 2 = 4In this case x² + y² = 2² + 2² = 4 + 4 = 8x = 1; y = 3(1) x + y = 4 holds true: 1 + 3 = 4In this case x² + y² = 1² + 3² = 1 + 9 = 10

 Author: questioner [ Fri Jan 25, 2013 4:29 am ] Post subject: Re: GMAT Algebra (Data Sufficiency) How can you combine statement 1 and 2 to make it match? Which product of XY that yields 2 has as sum 4?In other words, what are X and Y here?

 Author: Gennadiy [ Fri Jan 25, 2013 4:50 am ] Post subject: Re: GMAT Algebra (Data Sufficiency) Quote:In other words, what are X and Y here?There are two possible variants we can find from the system of the equations (1) and (2):x = 2 + √2 and y = 2 – √2orx = 2 – √2 and y = 2 + √2In any of the above variantsxy = (2 + √2)(2 – √2) = 2² – (√2)² = 4 – 2 = 2x + y = (2 + √2) + (2 – √2) = 4Note, that you do not need to find the actual values of x and y in this question. (Under the assumption that statements in a data sufficiency problem can not contradict each other. So (1) and (2) must define at least one value of (x, y) or more)

 Page 1 of 1 All times are UTC - 5 hours [ DST ] Powered by phpBB © 2000, 2002, 2005, 2007 phpBB Grouphttp://www.phpbb.com/